Fee charging in Nigerian academic libraries;" what justification? (1993)
This paper examines the issue of charging as it affects Nigerian Academic Libraries, The issue is looked at from the economic, socio-cultural and political viewpoints, Because of its complexity from the three perspectives mentioned above, it was concluded that while-Generalized Library services could be made free, charging can be introduced for Personalized Library Services and information Services, However, a clear distinction must be made between these three categories of services